Preparation method and application of iron-cobalt sulfide / nitrogen-doped carbon composite material based on spray drying method
The preparation of ZIF-67 skeleton derived iron-cobalt sulfide/nitrogen doped carbon composite material was solved by spray drying, which solved the problems of complex preparation process and high cost in the prior art, and achieved efficient preparation and excellent performance of sodium ion battery negative electrode materials.
Patent Information
- Application Number
- CN202411788930.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-06
AI Technical Summary
In the prior art, when preparing transition metal sulfide heterojunction/carbon composites, there are problems such as complex preparation process, high cost, long time consumption and low capacity retention of sodium ion half-cells.
The ZIF-67 skeleton derived iron-cobalt sulfide/nitrogen doped carbon composite was prepared by spray drying. The precursor solution was atomized into tiny droplets by spray drying, and the droplets were cured into particles by rapid evaporation at high temperature, followed by iron ion exchange and vapor phase vulcanization to form a nano-scale iron-cobalt sulfide/nitrogen doped carbon composite.
The preparation process is simplified and efficient, the cost is reduced, the particle size control and morphological uniformity of the material are improved, and the rate performance and cycle stability of the negative electrode material of sodium ion battery are enhanced.
Smart Images

Figure CN119612607A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to a method for preparing a ZIF-67 framework-derived iron-cobalt sulfide / nitrogen-doped carbon composite material based on a spray drying method and an application of the composite material as a negative electrode material for a sodium ion battery. Background Art
[0002] Lithium-ion batteries are widely used in portable energy storage, electric vehicles and other fields due to their advantages such as high energy density, long life, high charge and discharge efficiency and low pollution. However, the problems of uneven resource distribution and rising costs have gradually become prominent. In contrast, sodium is abundant and has similar chemical properties to lithium. Therefore, sodium-ion batteries have also been widely studied and are considered to be the most likely energy storage system to replace lithium-ion batteries. Carbon materials are the most widely studied negative electrode materials for sodium-ion batteries. Similar to lithium-ion batteries, carbon materials have excellent electrical conductivity and structural stability, making them one of the ideal negative electrode materials. However, the theoretical sodium storage capacity of carbon materials is limited. Therefore, finding new negative electrode materials to improve the performance of sodium-ion batteries is a hot topic in current research.
[0003] Transition metal sulfur compounds have become a hot topic in negative electrode material research due to their high theoretical capacity, abundant reserves, and no pollution. However, this type of material has problems such as poor conductivity and volume expansion during sodium storage, resulting in insufficient rate performance and cycle stability. Studies have found that the built-in electric field generated by the coupling of two crystals with different band gaps can promote charge transfer and improve the ion transfer rate, while carbon coating can not only serve as a fast electron transport layer, but also inhibit the volume change of the material during the charge and discharge process and improve the cycle stability of the material. Therefore, the preparation of transition metal sulfide heterojunction / carbon composite materials is a modification method that can effectively solve the above problems.
[0004] At present, there are methods based on solvothermal method, electrospinning method, mechanical ball milling method, etc. to prepare transition metal sulfide heterojunction / carbon composite materials. For example, patent CN114094078A uses bismuth source, molybdenum source and sulfur source as raw materials, and prepares nitrogen-doped carbon-coated metal sulfide heterostructure p-MoS through hydrothermal reaction and calcination process. 2 / n-Bi 2 S 3 @NC composite electrode materials, but the preparation process is complicated, the manufacturing cost is high, and the time is long. In addition, the capacity retention rate of the sodium ion half-battery composed of this electrode material is also low. In view of the above problems, it is necessary to study a simple and easy-to-operate preparation method that can achieve carbon coating and construct a heterogeneous structure to obtain stable and excellent sodium storage performance. Summary of the invention
[0005] In order to solve the deficiencies in the prior art, the present invention provides a method for preparing a ZIF-67 skeleton-derived iron-cobalt sulfide / nitrogen-doped carbon composite material based on a spray drying method and its application as a negative electrode material for a sodium ion battery. The iron-cobalt sulfide / nitrogen-doped carbon composite material of the present invention is first prepared by a spray drying method for ZIF-67, and then formed by iron ion exchange and subsequent gas phase sulfidation based on a ZIF-67 skeleton-derived iron-cobalt sulfide / nitrogen-doped carbon composite material, and the composite material has excellent rate performance and cycle stability when used as a negative electrode material for a sodium ion battery.
[0006] The specific technical scheme of the present invention is:
[0007] In a first aspect, the present invention provides a method for preparing a ZIF-67 framework-derived iron-cobalt sulfide / nitrogen-doped carbon composite material based on a spray drying method, comprising the following steps:
[0008] (1) dissolving a certain amount of 2-methylimidazole and cobalt salt in deionized water respectively, then quickly pouring the 2-methylimidazole solution into the cobalt salt solution, and stirring evenly to obtain a mixed solution A;
[0009] (2) spray drying the mixed solution A obtained in step (1) to obtain a purple precursor powder B;
[0010] (3) dispersing the purple precursor powder B obtained in step (2) in an alcohol solvent, soaking and recrystallizing it, and then adding iron salt to carry out ion exchange, standing for a period of time, centrifuging, washing, and drying to obtain an intermediate product C, namely Fe / ZIF-67;
[0011] (4) placing the intermediate product C obtained in step (3) and the sulfur powder at two ends of a porcelain boat respectively, and performing vapor phase sulfurization under an inert atmosphere to obtain a nanoscale iron-cobalt sulfide / nitrogen-doped carbon composite material with a polyhedral (mainly dodecahedral) morphology.
[0012] In the above steps, the present invention mixes 2-methylimidazole and cobalt salt to form a mixed solution A and then spray-dries it; during the spray-drying process, as the water in the droplets evaporates, the concentration of the metal-ligand complex formed by 2-methylimidazole and cobalt salt in the mixed solution A gradually increases, forming a saturation on the surface of the droplets, and this saturation is getting higher and higher, and finally forming a precursor spherical particle with a size of several microns. The precursor is an intermediate coordination compound of cobalt and 2-methylimidazole, which has an amorphous characteristic. Subsequently, during the immersion process of alcohol solvents, the compound nucleates and gradually recrystallizes into a ZIF-67 structure with a polyhedral (mainly dodecahedral) morphology. Subsequently, by ion exchange with iron ions in iron salts, Fe / ZIF-67 materials can be formed. Finally, a vapor phase sulfurization treatment is carried out under the protection of an inert atmosphere. During the vapor phase sulfurization process, the nitrogen-doped carbon framework derived from Fe / ZIF-67 provides a good conductive network and plays a role in limiting the agglomeration of metal sulfide particles. At the same time, iron and cobalt react with sulfur to generate iron-cobalt sulfide, and finally obtain a nano-scale iron-cobalt sulfide / nitrogen-doped carbon composite material with a dodecahedral morphology.
[0013] In the prior art, ZIF-67 materials are usually prepared using a traditional hydrothermal method. The present invention finds that the ZIF-67 particles prepared by this method have a larger particle size, about 1 μm, and exhibit thin-walled or hollow characteristics. The present invention finds that when prepared by spray drying, the particle size of the resulting product is significantly reduced to about 200-400 nm, and the morphology is uniform, regular and compact. This material is more suitable as a negative electrode material for sodium ion batteries. After analysis, this significant difference mainly stems from the difference in the reaction mechanism of the two preparation methods. The core feature of the spray drying method is to atomize the precursor solution into tiny droplets and solidify the droplets into particles by high-temperature rapid evaporation. In this process, the droplet evaporation rate is fast and uniform, which avoids the agglomeration or migration of particles during the growth process, thereby generating particles with smaller particle size and denser structure. In addition, the rapid drying mechanism of spray drying effectively suppresses the separation effect of internal and external components of the material, making the distribution of the components of the particles more uniform. In contrast, the hydrothermal method relies on ion diffusion, crystal nucleation and growth processes in the solution. Due to the long reaction time and relatively complex reaction kinetics, particles are prone to agglomeration, resulting in an increase in particle size. In addition, during the hydrothermal reaction, affected by the migration of solutes in and out, thin walls or hollow structures are easily formed on the surface of the particles, and the morphology lacks compactness. This phenomenon reflects the imbalance between the ion diffusion and crystal growth rate of the hydrothermal reaction.
[0014] Preferably, in step (1), the cobalt salt is one or more of cobalt sulfate, cobalt chloride or cobalt acetate.
[0015] The present invention accidentally discovered during the research process that the type of cobalt salt has an important influence on whether spray drying can be carried out smoothly. For example, when cobalt nitrate is used, no powder particles are produced in the spray drying collection unit, but a viscous gel is obtained near the outlet of the cyclone, indicating that cobalt nitrate is not suitable for the spray drying process system. In contrast, when cobalt sulfate, cobalt chloride or cobalt acetate are selected as cobalt salts, the spray drying process can be successfully completed, and the particle morphology is good; analysis shows that the reason may be related to the physicochemical properties of the cobalt salt and the evaporation behavior of the solution during the spray drying process. Cobalt nitrate may have undergone premature chemical reactions or gelation during the drying process, resulting in the failure of the particles to form normally, while the evaporation and nucleation behaviors of cobalt sulfate, cobalt chloride and cobalt acetate are more stable, thereby ensuring the successful generation of particles.
[0016] Preferably, in step (1), the molar ratio of 2-methylimidazole to cobalt salt is controlled to be 1:(0.25-0.9).
[0017] The present invention finds that the molar ratio of 2-methylimidazole to cobalt salt has an important influence on the formation of ZIFs. Specifically, an appropriate amount of excess 2-methylimidazole is required in the spray drying synthesis process to effectively complete the deprotonation reaction of ZIFs, ensuring that a pure crystalline phase material is finally obtained. This phenomenon can be attributed to the key role of ligands in the formation of ZIFs. 2-methylimidazole is not only a structural unit of ZIFs, but also coordinates with cobalt ions through a deprotonation reaction in the solution, thereby realizing the formation of a framework structure. When the content of 2-methylimidazole is insufficient, the degree of deprotonation is low, resulting in incomplete crystal growth or mixed phase generation. Excessive 2-methylimidazole can provide sufficient ligand molecules, further drive the deprotonation process and stabilize the framework structure, thereby forming a pure crystalline phase.
[0018] Preferably, in step (3), the mass ratio of the iron salt to the purple precursor powder B is (0.1-0.3):1.
[0019] The present invention further found that the ratio of iron salt to purple precursor powder B has a significant effect on the morphology of the material. When the Fe content is low, the framework structure of ZIF-67 remains basically intact, the material morphology is uniform, and the performance is excellent. However, with the increase of Fe content, the morphology of the material gradually changes, and the phenomenon of partial collapse of the framework or uneven structure may occur, which in turn has an adverse effect on its performance. This shows that the amount of Fe introduced needs to be strictly controlled to optimize the material performance while maintaining the stability of the framework structure. This phenomenon may be related to the substitution behavior of Fe during the ion exchange process. An appropriate amount of Fe substitution may only affect the local framework structure, while excessive Fe may lead to over-substitution or destroy the stability of the metal organic framework, thereby causing morphological changes and affecting the performance of the material.
[0020] Preferably, in step (1), the uniform mixing is performed by stirring at room temperature for 5 to 30 minutes.
[0021] Preferably, in step (2), the inlet air temperature of the spray drying process is 180-200°C, the outlet air temperature is 90-110°C, and the feed rate is 5-15 mL min -1 .
[0022] The present invention found that a too fast feed rate will prevent the complete formation of the particles and increase the risk of agglomeration; a too slow feed rate may cause irregular particle shapes, prolong drying time, increase energy consumption and reduce production efficiency. Therefore, controlling the appropriate temperature and feed rate is crucial to ensure particle quality and improve production efficiency.
[0023] Preferably, in step (3), the alcohol solvent is one or more of ethanol, methanol and isopropanol.
[0024] Preferably, in step (3), the iron salt is ferric chloride and / or ferric nitrate.
[0025] Preferably, in step (3), the standing temperature is room temperature and the standing time is 1 to 12 hours.
[0026] Preferably, in step (3), the recrystallization time is 0.5 to 6 hours.
[0027] Preferably, in step (4), the mass ratio of the intermediate product C to the sulfur powder is 1; (3-5), the temperature of the gas phase vulcanization is 300-500° C., and the holding time is 1-3 h.
[0028] In a second aspect, the present invention provides the use of the iron-cobalt sulfide / nitrogen-doped carbon composite material obtained by the above preparation method as a negative electrode material for a sodium ion battery.
[0029] Compared with the prior art, the beneficial effects of the present invention are:
[0030] (1) The present invention prepares nanoscale ZIF-67 skeleton materials by spray drying, which is simple and efficient compared to the traditional liquid phase method, has high repeatability, low cost, and is more suitable for large-scale production.
[0031] (2) The ZIF-67 skeleton material synthesized by the present invention has a relatively regular morphology and is in the form of dodecahedral nanoparticles with a relatively stable structure, and is more likely to be used as a functional template and precursor in the field of energy storage.
[0032] (3) The present invention uses ZIF-67 as a template, loads iron ions onto ZIF-67 through ion exchange, and then obtains an iron-cobalt sulfide heterojunction through a one-step gas-phase sulfidation method. The built-in electric field constructed by this heterostructure can significantly improve the ion diffusion kinetics.
[0033] (4) The nitrogen-doped carbon matrix formed during the one-step gas phase sulfurization treatment of the present invention is not only beneficial to improving the conductivity of the composite material, but also can effectively alleviate the volume expansion and contraction of the iron-cobalt sulfide heterojunction during the electrochemical reaction, which helps to improve the electrochemical stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is a scanning electron microscope image of the cobalt sulfide / nitrogen-doped carbon composite material prepared in Comparative Example 1.1;
[0035] Figure 2 is a scanning electron microscope image of the iron-cobalt sulfide / nitrogen-doped carbon composite material prepared in Example 1;
[0036] Figure 3 is a scanning electron microscopy image of ZIF-67 prepared in Example 2.1;
[0037] Figure 4 This is a battery rate performance diagram of the iron-cobalt sulfide / nitrogen-doped carbon composite material prepared in Example 2.2;
[0038] Figure 5 is the X-ray diffraction pattern of ZIF-67 prepared in Example 2.3;
[0039] Figure 6 is a scanning electron microscope image of Fe / ZIF-67 prepared in Example 3.1;
[0040] Figure 7 is a scanning electron microscope image of Fe / ZIF-67 prepared in Example 3.2;
[0041] Figure 8 is an X-ray diffraction pattern of the iron-cobalt sulfide / nitrogen-doped carbon composite material prepared in Example 3.2;
[0042] Fig. 9 is a scanning electron microscope image of Fe / ZIF-67 prepared in Comparative Example 3;
[0043] Fig.10 is a scanning electron microscope image of the iron-cobalt sulfide / nitrogen-doped carbon composite material prepared in Example 4.1;
[0044] Fig.11 This is a battery cycle performance diagram of the iron-cobalt sulfide / nitrogen-doped carbon composite material prepared in Example 4.1;
[0045] Fig.12 is a scanning electron microscope image of the iron-cobalt sulfide / nitrogen-doped carbon composite material prepared in Example 4.2;
[0046] Fig.13This is a scanning electron microscope image of the iron-cobalt sulfide / nitrogen-doped carbon composite material prepared in Comparative Example 4. DETAILED DESCRIPTION
[0047] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited thereto.
[0048] (I) Comparison between traditional hydrothermal method and spray drying method
[0049] Comparative Example 1.1
[0050] (1) 32 mmol of 2-methylimidazole and 16 mmol of cobalt acetate were dissolved in 50 mL of anhydrous methanol respectively, and the 2-methylimidazole solution was quickly poured into the cobalt acetate solution after stirring at room temperature for 5 min to obtain a mixed solution A;
[0051] (2) placing the mixed solution A obtained in step (1) into a polytetrafluoroethylene reaction liner, reacting at 60° C. for 24 h, centrifuging, washing, and drying to obtain an intermediate product B, namely, ZIF-67 material;
[0052] (3) The intermediate product B obtained in step (2) and sulfur powder are placed at both ends of a porcelain boat in a mass ratio of 1:4, and vapor-phase sulfurized at 500° C. for 2 h in a nitrogen atmosphere to obtain a cobalt sulfide / nitrogen-doped carbon composite material.
[0053] Comparative Example 1.2
[0054] (1) 32 mmol of 2-methylimidazole and 8 mmol of cobalt acetate were dissolved in 50 mL of deionized water, respectively. After stirring at room temperature for 5 min, the 2-methylimidazole solution was quickly poured into the cobalt acetate solution to obtain a mixed solution A;
[0055] (2) placing the mixed solution A obtained in step (1) into a polytetrafluoroethylene reaction liner, reacting at 60° C. for 24 h, centrifuging, washing, and drying to obtain an intermediate product B, namely, ZIF-67 material;
[0056] (3) Dispersing 1 g of the intermediate product B obtained in step (2) in anhydrous methanol solvent, soaking and recrystallizing for 0.5 h, adding 0.2 mmol of ferric chloride for ion exchange, standing at room temperature for 6 h, centrifuging, washing, and drying to obtain the intermediate product C, i.e., Fe / ZIF-67;
[0057] (4) The intermediate product C obtained in step (3) and sulfur powder are placed at both ends of a porcelain boat in a mass ratio of 1:5, and vapor-phase sulfurized at 500° C. for 3 h in a nitrogen atmosphere to obtain an iron-cobalt sulfide / nitrogen-doped carbon composite material.
[0058] Example 1
[0059] (1) 32 mmol of 2-methylimidazole and 8 mmol of cobalt acetate were dissolved in 50 mL of deionized water, respectively. After stirring at room temperature for 5 min, the 2-methylimidazole solution was quickly poured into the cobalt acetate solution to obtain a mixed solution A;
[0060] (2) The mixed solution A obtained in step (1) was spray dried to obtain a purple precursor powder B. The inlet air temperature of the spray drying process was 190°C, the outlet air temperature was 100°C, and the feed rate was 15 mL min -1 ;
[0061] (3) Dispersing 1 g of the purple precursor powder B obtained in step (2) in anhydrous methanol solvent, soaking and recrystallizing for 0.5 h, adding 0.2 mmol of ferric chloride for ion exchange, standing at room temperature for 6 h, centrifuging, washing, and drying to obtain the intermediate product C, namely Fe / ZIF-67;
[0062] (4) The intermediate product C obtained in step (3) and sulfur powder are placed at both ends of a porcelain boat in a mass ratio of 1:5, and vapor-phase sulfurized at 500° C. for 3 h in a nitrogen atmosphere to obtain an iron-cobalt sulfide / nitrogen-doped carbon composite material.
[0063] Comparison of results: By comparing the experimental results of Comparative Example 1.1, Comparative Example 1.2 and Example 1, it is found that the particle size of the particles prepared by the traditional hydrothermal method in Comparative Example 1.1 is larger, such as Figure 1 The particle size of the particles prepared by the spray drying method in Example 1 is significantly reduced to about 300 nm ( Figure 2), and the morphology is uniform and compact. This significant difference is mainly due to the essential differences in the reaction mechanisms of the two preparation methods. The core feature of the spray drying method is to atomize the precursor solution into tiny droplets, and solidify the droplets into particles through high-temperature rapid evaporation. In this process, the droplet evaporation rate is fast and uniform, which avoids the agglomeration or migration of particles during growth, thereby generating particles with smaller particle size and denser structure. In addition, the rapid drying mechanism of spray drying effectively suppresses the separation effect of internal and external components of the material, making the component distribution of the particles more uniform. In contrast, the hydrothermal method relies on ion diffusion, crystal nucleation and growth processes in the solution. Due to the long reaction time and relatively complex reaction kinetic conditions, the particles are prone to agglomeration, resulting in an increase in particle size. In addition, during the hydrothermal reaction process, affected by the migration of solutes inside and outside, the surface of the particles is prone to form thin walls or hollow structures, and the morphology lacks compactness. This phenomenon reflects the imbalance between the ion diffusion and crystal growth rate of the hydrothermal reaction. In summary, the spray drying method not only shows significant advantages in particle size control, but also effectively improves the uniformity and density of particle morphology. The rapid evaporation characteristics of this method provide important support for the microstructure optimization of materials, while the traditional hydrothermal method is relatively inadequate in terms of particle size and morphology control due to the limitations of the reaction mechanism.
[0064] (II) Comparison of different cobalt salts
[0065] Example 2.1 (Cobalt Acetate)
[0066] (1) 32 mmol of 2-methylimidazole and 8 mmol of cobalt acetate were dissolved in 50 mL of deionized water, respectively. After stirring at room temperature for 5 min, the 2-methylimidazole solution was quickly poured into the cobalt acetate solution to obtain a mixed solution A;
[0067] (2) The mixed solution A obtained in step (1) is spray dried to obtain a purple precursor powder B. The inlet air temperature of the spray drying process is 200°C, the outlet air temperature is 110°C, and the feed rate is 10 mL min -1 ;
[0068] (3) Dispersing 1 g of the purple precursor powder B obtained in step (2) in anhydrous methanol solvent, soaking and recrystallizing for 0.5 h, adding 0.1 mmol of ferric chloride for ion exchange, standing at room temperature for 3 h, centrifuging, washing, and drying to obtain the intermediate product C, namely Fe / ZIF-67;
[0069] (4) The intermediate product C obtained in step (3) and sulfur powder are placed at both ends of a porcelain boat in a mass ratio of 1:5, and vapor-phase sulfurized at 400° C. for 3 h in a nitrogen atmosphere to obtain an iron-cobalt sulfide / nitrogen-doped carbon composite material.
[0070] Comparative Example 2 (cobalt nitrate)
[0071] (1) 32 mmol of 2-methylimidazole and 8 mmol of cobalt nitrate were dissolved in 50 mL of deionized water, respectively. After stirring at room temperature for 5 min, the 2-methylimidazole solution was quickly poured into the cobalt nitrate solution to obtain a mixed solution A;
[0072] (2) The mixed solution A obtained in step (1) was spray-dried to obtain a purple viscous gel-like substance Example 2.2 (cobalt chloride)
[0073] (1) 32 mmol of 2-methylimidazole and 8 mmol of cobalt chloride were dissolved in 50 mL of deionized water, respectively. After stirring at room temperature for 5 min, the 2-methylimidazole solution was quickly poured into the cobalt chloride solution to obtain a mixed solution A;
[0074] (2) The mixed solution A obtained in step (1) is spray dried to obtain a purple precursor powder B. The inlet air temperature of the spray drying process is 200°C, the outlet air temperature is 110°C, and the feed rate is 10 mL min -1 ;
[0075] (3) Dispersing 1 g of the purple precursor powder B obtained in step (2) in anhydrous methanol solvent, soaking and recrystallizing for 0.5 h, adding 0.1 mmol of ferric chloride for ion exchange, standing at room temperature for 3 h, centrifuging, washing, and drying to obtain the intermediate product C, namely Fe / ZIF-67;
[0076] (4) The intermediate product C obtained in step (3) and sulfur powder are placed at both ends of a porcelain boat in a mass ratio of 1:5, and vapor-phase sulfurized at 400° C. for 3 h in a nitrogen atmosphere to obtain an iron-cobalt sulfide / nitrogen-doped carbon composite material.
[0077] Example 2.3 (Cobalt sulfate)
[0078] (1) 32 mmol of 2-methylimidazole and 8 mmol of cobalt sulfate were dissolved in 50 mL of deionized water, respectively. After stirring at room temperature for 5 min, the 2-methylimidazole solution was quickly poured into the cobalt sulfate solution to obtain a mixed solution A;
[0079] (2) The mixed solution A obtained in step (1) is spray dried to obtain a purple precursor powder B. The inlet air temperature of the spray drying process is 200°C, the outlet air temperature is 110°C, and the feed rate is 10 mL min -1 ;
[0080] (3) Dispersing 1 g of the purple precursor powder B obtained in step (2) in anhydrous methanol solvent, soaking and recrystallizing for 0.5 h, adding 0.1 mmol of ferric chloride for ion exchange, standing at room temperature for 3 h, centrifuging, washing, and drying to obtain the intermediate product C, namely Fe / ZIF-67;
[0081] (4) The intermediate product C obtained in step (3) and sulfur powder are placed at both ends of a porcelain boat in a mass ratio of 1:5, and vapor-phase sulfurized at 400° C. for 3 h in a nitrogen atmosphere to obtain an iron-cobalt sulfide / nitrogen-doped carbon composite material.
[0082] From the comparison of the experimental results of Comparative Example 2 and Examples 2.1-2.3, it can be seen that when cobalt nitrate was used in Comparative Example 2, powder particles could not be obtained in the collection unit during the spray drying process, but a viscous gel-like substance was formed near the cyclone outlet, indicating that cobalt nitrate is not suitable for this spray drying process system. In contrast, when cobalt acetate, cobalt chloride and cobalt sulfate were selected as cobalt salts in Examples 2.1-2.3, the spray drying process was successfully completed to obtain powder materials with good particle morphology (such as Figure 3 As shown). Therefore, in the present invention, the applicable cobalt salt is any one of cobalt sulfate, cobalt chloride or cobalt acetate. This phenomenon may be related to the physicochemical properties of the cobalt salt and the evaporation behavior of the solution during the spray drying process. Cobalt nitrate may undergo premature chemical reaction or gelation during the drying process, resulting in the failure of normal particle formation, while the evaporation and nucleation behavior of cobalt sulfate, cobalt chloride and cobalt acetate are more stable, thereby ensuring the successful generation of particles.
[0083] (III) Comparison of different molar ratios of dimethylimidazole (2-MIM) and cobalt salt
[0084] Example 3.1 (2-methylimidazole: cobalt acetate = 32:8)
[0085] (1) 32 mmol of 2-methylimidazole and 8 mmol of cobalt acetate were dissolved in 50 mL of deionized water, respectively. After stirring at room temperature for 5 min, the 2-methylimidazole solution was quickly poured into the cobalt acetate solution to obtain a mixed solution A;
[0086] (2) The mixed solution A obtained in step (1) is spray dried to obtain a purple precursor powder B. The inlet air temperature of the spray drying process is 180°C, the outlet air temperature is 90°C, and the feed rate is 10 mL min -1 ;
[0087] (3) Dispersing 1 g of the purple precursor powder B obtained in step (2) in anhydrous methanol solvent, soaking and recrystallizing for 0.5 h, adding 0.1 mmol of ferric chloride for ion exchange, standing at room temperature for 1 h, centrifuging, washing, and drying to obtain the intermediate product C, namely Fe / ZIF-67;
[0088] (4) The intermediate product C obtained in step (3) and sulfur powder are placed at both ends of a porcelain boat in a mass ratio of 1:4, and vapor-phase sulfurized at 500° C. for 2 h in a nitrogen atmosphere to obtain an iron-cobalt sulfide / nitrogen-doped carbon composite material.
[0089] Example 3.2 (2-methylimidazole: cobalt acetate = 32:16)
[0090] (1) 32 mmol of 2-methylimidazole and 16 mmol of cobalt acetate were dissolved in 50 mL of deionized water, respectively. After stirring at room temperature for 5 min, the 2-methylimidazole solution was quickly poured into the cobalt acetate solution to obtain a mixed solution A;
[0091] (2) The mixed solution A obtained in step (1) is spray dried to obtain a purple precursor powder B. The inlet air temperature of the spray drying process is 180°C, the outlet air temperature is 90°C, and the feed rate is 10 mL min -1 ;
[0092] (3) Dispersing 1 g of the purple precursor powder B obtained in step (2) in anhydrous methanol solvent, soaking and recrystallizing for 0.5 h, adding 0.1 mmol of ferric chloride for ion exchange, standing at room temperature for 1 h, centrifuging, washing, and drying to obtain the intermediate product C, namely Fe / ZIF-67;
[0093] (4) The intermediate product C obtained in step (3) and sulfur powder are placed at both ends of a porcelain boat in a mass ratio of 1:4, and vapor-phase sulfurized at 500° C. for 2 h in a nitrogen atmosphere to obtain an iron-cobalt sulfide / nitrogen-doped carbon composite material.
[0094] Comparative Example 3 (2-methylimidazole: cobalt acetate = 32:32)
[0095] (1) 32 mmol of 2-methylimidazole and 32 mmol of cobalt acetate were dissolved in 50 mL of deionized water, respectively. After stirring at room temperature for 5 min, the 2-methylimidazole solution was quickly poured into the cobalt acetate solution to obtain a mixed solution A;
[0096] (2) The mixed solution A obtained in step (1) is spray dried to obtain a purple precursor powder B. The inlet air temperature of the spray drying process is 180°C, the outlet air temperature is 90°C, and the feed rate is 10 mL min -1 ;
[0097] (3) Dispersing 1 g of the purple precursor powder B obtained in step (2) in anhydrous methanol solvent, soaking and recrystallizing for 0.5 h, adding 0.1 mmol of ferric chloride for ion exchange, standing at room temperature for 1 h, centrifuging, washing, and drying to obtain the intermediate product C, namely Fe / ZIF-67;
[0098] (4) The intermediate product C obtained in step (3) and sulfur powder are placed at both ends of a porcelain boat in a mass ratio of 1:4, and vapor-phase sulfurized at 500° C. for 2 h in a nitrogen atmosphere to obtain an iron-cobalt sulfide / nitrogen-doped carbon composite material.
[0099] In the above case, the molar ratio of dimethylimidazole (2-MIM) to cobalt salt was adjusted to investigate its effect on the formation of ZIFs. Figure 6 (Example 3.1), Figure 7 (Example 3.2) and Fig. 9 As shown in the results of (Comparative Example 3), an appropriate amount of excess 2-MIM is required during the synthesis process to effectively complete the deprotonation reaction of ZIFs, ensuring that a pure crystalline phase material is finally obtained. This phenomenon can be attributed to the key role of ligands in the formation of ZIFs. 2-MIM is not only a structural unit of ZIFs, but also coordinates with metal ions (such as cobalt ions) through a deprotonation reaction in the solution, thereby achieving the formation of a framework structure. When the 2-MIM content is insufficient (Comparative Example 3), the degree of deprotonation is low, resulting in incomplete crystal growth or mixed phase generation. Excessive 2-MIM can provide sufficient ligand molecules to further drive the deprotonation process and stabilize the framework structure, thereby forming a pure crystalline phase.
[0100] (IV) Comparison of different iron contents
[0101] Example 4.1 (mass ratio of purple precursor powder B: ferric chloride = 62:1)
[0102] (1) 32 mmol of 2-methylimidazole and 8 mmol of cobalt chloride were dissolved in 50 mL of deionized water, respectively. After stirring at room temperature for 5 min, the 2-methylimidazole solution was quickly poured into the cobalt chloride solution to obtain a mixed solution A;
[0103] (2) The mixed solution A obtained in step (1) is spray dried to obtain a purple precursor powder B. The inlet air temperature of the spray drying process is 200°C, the outlet air temperature is 110°C, and the feed rate is 10 mL min -1 ;
[0104] (3) Dispersing 1 g of the purple precursor powder B obtained in step (2) in anhydrous methanol solvent, soaking and recrystallizing for 0.5 h, adding 0.1 mmol of ferric chloride for ion exchange, standing at room temperature for 6 h, centrifuging, washing, and drying to obtain the intermediate product C, namely Fe / ZIF-67;
[0105] (4) The intermediate product C obtained in step (3) and sulfur powder are placed at both ends of a porcelain boat in a mass ratio of 1:5, and vapor-phase sulfurized at 500° C. for 3 h in a nitrogen atmosphere to obtain an iron-cobalt sulfide / nitrogen-doped carbon composite material.
[0106] Example 4.2 (mass ratio of purple precursor powder B: ferric chloride = 31:1)
[0107] (1) 32 mmol of 2-methylimidazole and 8 mmol of cobalt chloride were dissolved in 50 mL of deionized water, respectively. After stirring at room temperature for 5 min, the 2-methylimidazole solution was quickly poured into the cobalt chloride solution to obtain a mixed solution A;
[0108] (2) The mixed solution A obtained in step (1) is spray dried to obtain a purple precursor powder B. The inlet air temperature of the spray drying process is 200°C, the outlet air temperature is 110°C, and the feed rate is 10 mL min -1 ;
[0109] (3) Dispersing 1 g of the purple precursor powder B obtained in step (2) in anhydrous methanol solvent, soaking and recrystallizing for 0.5 h, adding 0.2 mmol of ferric chloride for ion exchange, standing at room temperature for 6 h, centrifuging, washing, and drying to obtain the intermediate product C, namely Fe / ZIF-67;
[0110] (4) The intermediate product C obtained in step (3) and sulfur powder are placed at both ends of a porcelain boat in a mass ratio of 1:5, and vapor-phase sulfurized at 500° C. for 3 h in a nitrogen atmosphere to obtain an iron-cobalt sulfide / nitrogen-doped carbon composite material.
[0111] Comparative Example 4 (mass ratio of purple precursor powder B: ferric chloride = 21:1)
[0112] (1) 32 mmol of 2-methylimidazole and 8 mmol of cobalt chloride were dissolved in 50 mL of deionized water, respectively. After stirring at room temperature for 5 min, the 2-methylimidazole solution was quickly poured into the cobalt chloride solution to obtain a mixed solution A;
[0113] (2) The mixed solution A obtained in step (1) is spray dried to obtain a purple precursor powder B. The inlet air temperature of the spray drying process is 200°C, the outlet air temperature is 110°C, and the feed rate is 10 mL min -1 ;
[0114] (3) Dispersing 1 g of the purple precursor powder B obtained in step (2) in anhydrous methanol solvent, soaking and recrystallizing for 0.5 h, adding 0.3 mmol of ferric chloride for ion exchange, standing at room temperature for 6 h, centrifuging, washing, and drying to obtain the intermediate product C, namely Fe / ZIF-67;
[0115] (4) The intermediate product C obtained in step (3) and sulfur powder are placed at both ends of a porcelain boat in a mass ratio of 1:5, and vapor-phase sulfurized at 500° C. for 3 h in a nitrogen atmosphere to obtain an iron-cobalt sulfide / nitrogen-doped carbon composite material.
[0116] In the above case, Fe / ZIF-67 material was successfully prepared by introducing iron for ion exchange. Fig.10(Example 4.1), Fig.12 (Example 4.2) and Fig.13 As shown in the results of (Comparative Example 4), the amount of Fe introduced has a significant effect on the morphology of the material. When the Fe content is low, the framework structure of ZIF-67 remains basically intact, the material morphology is uniform, and the performance is excellent. However, as the Fe content increases, the morphology of the material gradually changes, and the phenomenon of partial collapse of the framework or uneven structure may occur, which in turn has an adverse effect on its performance (Comparative Example 4). This shows that the amount of Fe introduced needs to be strictly controlled to optimize the material performance while maintaining the stability of the framework structure. This phenomenon may be related to the substitution behavior of Fe during the ion exchange process. An appropriate amount of Fe substitution may only affect the local framework structure, while excessive Fe may lead to excessive substitution or destroy the stability of the metal organic framework, thereby causing morphological changes and affecting the performance of the material.
[0117] Performance Testing
[0118] The final products of all the comparative examples and examples above were mixed with the conductive agent Super P, the binder polyvinylidene fluoride (PVDF) at a mass ratio of 7:2:1 and 2 mL of N-methylpyrrolidone (NMP) solvent to make a homogeneous slurry, and then evenly coated on the copper current collector, and after being dried at a constant temperature of 60°C for 12 hours, punched into 1.2 cm diameter discs as sodium ion battery electrodes. Then, glass fiber was used as a separator and 1.0 mol·L -1 NeA 6 As the solute, the electrolyte with diethylene glycol dimethyl ether (Diglyme) as the solvent and the metal sodium sheet as the counter electrode were assembled into a liquid half-cell. In a constant temperature environment of 25°C, the assembled sodium ion half-cell was left to stand for 12 hours, and then a constant current charge and discharge test was performed in the range of 0.01 to 3V.
[0119] Figure 1 This is the X-ray diffraction pattern of Example 3.2. Cobalt disulfide (JCPDS No. 89-3056) and iron disulfide (JCPDS No. 89-3057) in the figure confirm that an iron-cobalt sulfide heterojunction is formed after iron ion exchange. Figure 5 The X-ray diffraction pattern of Example 2.3 shows that the ZIF-67 material can be successfully synthesized by a simple spray drying and short-time alcohol soaking process. Figure 3 From the scanning electron microscopy image, it can be found that the prepared ZIF-67 presents a uniform polyhedral morphology with an average diameter of about 200nm.
[0120] Figure 4 The rate performance test results of Example 2.2 show that the sodium ion battery has a rate performance of 0.2Ag. -1 , 0.5Ag -1, 1Ag -1 , 2Ag -1 , 5Ag -1 And restore 0.2Ag -1 The specific capacity is 703 mAh g -1 、654mAhg -1 , 626mAh g -1 , 587mAh g -1 , 471mAh g -1 and 741mAh g -1 , showing excellent rate performance.
[0121] As shown in Table 1, for Examples 4.1-4.2 and Comparative Examples 1 and 4, the -1 The first cycle coulombic efficiency at a current density of and the reversible capacity and capacity retention rate after 100 cycles.
[0122] Table 1
[0123]
[0124] It can be seen from Table 1 that changing the amount of iron salt introduced will have a certain impact on the performance of the electrode material. Compared with Comparative Example 1, the performance of Examples 4.1-4.2 and Comparative Example 4 is greatly improved, which is attributed to the built-in electric field of the iron-cobalt sulfide heterostructure promoting the migration and diffusion of sodium ions in the material, thereby improving its electrochemical performance. When more iron salt is introduced, Fig.13 The scanning electron microscope image of the final product of Comparative Example 4, the iron-cobalt sulfide / nitrogen-doped carbon composite material, shows obvious accumulation, which is not conducive to the activation of the active sites of the material, resulting in its electrochemical performance being inferior to that of Examples 4.1 and 4.2. It is worth noting that Fig.11 The embodiment 4.1 shown has the highest capacity retention rate (99.4%) after 100 cycles. Fig.10 From the scanning electron microscope image of the final product, iron-cobalt sulfide / nitrogen-doped carbon composite material, it can be found that the product has a uniform polyhedral morphology with a particle size of about 200nm. This stable structure is conducive to improving its electrochemical stability. Figure 1 This is a scanning electron microscope image of the final product of Comparative Example 1.1, cobalt iron sulfide / nitrogen-doped carbon composite material, which shows a micrometer-scale hollow polyhedron morphology. This structure is easy to break and collapse during the charge and discharge process, which ultimately affects the electrochemical performance.
[0125] In summary, the preparation conditions of the precursor ZIF-67 of the Fe / ZIF-67 of the present invention are very simple. Compared with the traditional solvothermal method, the present invention can be prepared quickly and continuously, and the size of ZIF-67 can be reduced to the nanoscale, thereby enhancing the structural stability. In addition, the target iron-cobalt sulfide / nitrogen-doped carbon composite material can be obtained by high-temperature calcination at 500°C in a nitrogen atmosphere, without the generation of other by-products, and the preparation of the material has good economic and utilization benefits. The results in Table 1 show that when the amount of iron salt introduced is 0.1 mmol, the iron-cobalt sulfide / nitrogen-doped carbon composite material exhibits good electrochemical properties as a negative electrode material for sodium ion batteries, making it an effective method worthy of consideration in the preparation of sodium ion battery materials.
[0126] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0127] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing an iron-cobalt sulfide / nitrogen-doped carbon composite material based on a spray drying method, characterized in that The following steps are involved: (1) mixing a 2-methylimidazole aqueous solution with a cobalt salt aqueous solution to obtain a mixed solution A; wherein the cobalt salt is one or more of cobalt sulfate, cobalt chloride and cobalt acetate; and the molar ratio of the 2-methylimidazole to the cobalt salt is 1:(0.25-0.9); (2) spray drying the mixed solution A to obtain a purple precursor powder B; (3) dispersing the purple precursor powder B in an alcohol solvent, soaking and recrystallizing, then adding iron salt for ion exchange, standing, centrifuging, washing, and drying to obtain an intermediate product C, namely Fe / ZIF-67; wherein the mass ratio of the iron salt to the purple precursor powder B is (21-62):1; (4) The intermediate product C is subjected to vapor phase sulfurization with sulfur powder in an inert atmosphere to obtain a nano-scale iron-cobalt sulfide / nitrogen-doped carbon composite material with a polyhedral morphology.
2. The method according to claim 1, characterized in that: In step (1), the mixing is carried out by stirring at room temperature for 5 to 30 minutes.
3. The preparation method according to claim 1, characterized in that: In step (2), the inlet air temperature of the spray drying process is 180-200°C, the outlet air temperature is 90-110°C, and the feed rate is 5-15 mL min -1 .
4. The preparation method according to claim 1, characterized in that: In step (3), the alcohol solvent is one or more of ethanol, methanol and isopropanol.
5. The method according to claim 1, characterized in that: In step (3), the recrystallization time is 0.5 to 6 hours.
6. The preparation method according to claim 1, characterized in that: In step (3), the iron salt is ferric chloride and / or ferric nitrate.
7. The preparation method according to claim 1, characterized in that: In step (3), the standing temperature is room temperature and the standing time is 1 to 12 hours.
8. The preparation method according to claim 1, characterized in that: In step (4), the mass ratio of the intermediate product C to sulfur powder is 1:(3-5).
9. The preparation method according to claim 1, characterized in that: In step (4), the temperature of the gas phase vulcanization is 300 to 500° C., and the insulation time is 1 to 3 hours.
10. Use of the iron-cobalt sulfide / nitrogen-doped carbon composite material obtained by the preparation method according to any one of claims 1 to 9 in preparing negative electrode materials for sodium ion batteries.
Citation Information
Patent Citations
Zinc-cobalt sulfide / carbon nano negative electrode material and preparation method thereof
CN111293300A
Nickel cobalt-molybdenum disulfide hollow nano composite material as well as synthesis method and electrocatalytic hydrogen evolution application thereof
CN111992227A
Method for preparing FeS2 / C hollow microspheres based on spray drying and application of FeS2 / C hollow microspheres
CN118016850A
KR20240054843A
KR20240149273A
Cited By
Double-signal electrochemical uric acid sensor based on CoFe-coated NC composite material, preparation method of double-signal electrochemical uric acid sensor and application of double-signal electrochemical uric acid sensor in uric acid detection
CN120629302A